Tinjauan Hukum Perlindungan Hak Cipta Film Dokumenter Dan Peluang Hak Ekonomi Insan Perfilman Dokumenter Di Indonesia - Tamara Indratmo, Kadenza Adistya (UI Scholars Hub, 2022)
The film production process requires human resources (power) with certain qualifications according to their roles and functions. At a certain level, the personnel involved in film production must be professionals. One of the significant growths of the Indonesian film industry today is the growth in the number of cinema screens. In addition, new film genres have also emerged, so that the films shown by the public are increasingly diverse. One of these new genres is the documentary film as a cinematographic work which is also protected by Law Number 28 of 2014 concerning Copyright (UUHC). In the midst of such a heavy flow of mass media, documentary films have an important role as an independent aspirational medium. However, the issue of economic rights in cinematographic works apparently has not yet become a strategic discussion even though along with the development of information and communication technology, cinematographic works have a strategic role in the nation's economy. This research uses a combination of empirical legal research, normative legal research and descriptive research. The documentary film industry in Indonesia is still underdeveloped and depends on funders so that it affects the creative process in its production. In addition, legal awareness, especially in the field of copyright, by the filmmakers of the documentary film itself is still not optimally developed. Documentary filmmakers also have the opportunity to get royalties through agreements with producers. Suggestions from the author are government support for documentary filmmakers in addition to funding, legal awareness building and the establishment of a Collective Management Institute in the film sector.